Organizing Bandung Isola Performing Arts Festival (BIPAF) As A Market of Innovative Performing Arts in Indonesia - Sukmayadi, Yudi; Masunah, Juju (Harmonia: Journal of Arts Research and Education, 2020)
The purpose of this article is to discuss a festival model which promotes innovative performing arts in Indonesia. This qualitative approach used a project-based research method. The procedure of this research began with diagnosing the problems, making plan to conduct the festival in Bandung, conducting the festival, and evaluation. Data were collected by participation observation, interview, study of documentation, focused group discussion, and personal reflection. The findings of this research showed that Bandung Isola Performing Arts Festival (BIPAF) is a festival model as a form of market for innovative performing arts. The activities of BIPAF began with selecting/curating the performing artworks, holding art incubation, making promotion, show casing and pitching, as well as discussion and evaluation. BIPAF organizer designed a meeting within choreographers/producers and festival directors, curators and promotors of performing arts in Villa Isola outdoor stage in Universiatas Pendididkan Indonesia. This meeting was followed up by performing some pieces from BIPAF in the stage of SIPA and IMF Surakarta, and Korean Festival in South Korea. This festival contains a strategy value to develop creative industry sub sector of performing arts in Indonesia.